Promising outcomes from a cognitive behavioral therapy text-messaging intervention targeting drug use, antiretroviral therapy adherence, and HIV risk behaviors among adults living with HIV and substance use disorders. (1st February 2022) - Glasner, Suzette; Patrick, Kevin; Ybarra, Michele; Reback, Cathy J.; Ang, Alfonso; Kalichman, Seth; Bachrach, Ken; Garneau, Hélène Chokron; Venegas, Alexandra; Rawson, Richard A.
Abstract: Background: To date, no studies have reported the use of text messaging to deliver cognitive behavioral therapy (CBT) to people living with HIV and substance use disorders. Objective: We developed and evaluated a 12-week, CBT-based text-messaging intervention (TXT-CBT) targeting drug use and adherence to antiretroviral therapy (ART) for adults with HIV and comorbid opioid and stimulant use disorders. Materials and methods: Participants were randomly assigned to receive either TXT-CBT (n = 25) or an informational pamphlet (INFO) discussing substance use and medication adherence (n = 25). ART adherence, drug use, and HIV-risk behaviors were assessed at baseline, monthly during treatment, and treatment-end, and were compared between groups using a mixed-model repeated-measures analysis. Injection drug use was examined as a moderator of outcomes. Results: Relative to the INFO group, TXT-CBT participants evidenced increased ART adherence, measured by phone-based unannounced pill counts and biochemically by viral load and CD4 count. TXT-CBT participation was also associated with reductions in opioid use and HIV risk behaviors. While reductions in cocaine use were observed in the TXT-CBT group, relative to the INFO group, other stimulant use did not change. Among people who inject drugs, TXT-CBT produced increases in ART adherence and corresponding changes in viral load, relative to injection drug users in the control condition. Conclusions: Findings demonstrated promising preliminary evidence for the efficacy of TXT-CBT in improving ART adherence and reducing drug use and HIV-risk behaviors among people with HIV infection and comorbid opioid and stimulant use disorders. Highlights: No studies have delivered CBT to individuals with opioid and stimulant use disorders and HIV using text messaging. Those who received TXT-CBT evidenced reductions in cocaine and opioid use and increased antiretroviral therapy adherence. Those who received TXT-CBT reduced HIV-risk behaviors and increased their self-efficacy related to medication adherence. TXT-CBT is a potentially scalable intervention for people living with HIV and opioid and/or cocaine use disorders.